Teacher’s Elicitation Techniques in English for Nursing: A Classroom Interaction Analysis - Alpian Haju; Nurlaila Husain; Haris Danial (Universitas Islam Negeri Palopo, 2026)
This study describes the types of elicitation techniques used by an English teacher during classroom interaction in English for Nursing learning at SMK Negeri 1 Bulango Selatan. This research employed a qualitative case study design. Data were collected through five classroom observations and video recordings involving one English teacher who taught eleventh-grade nursing students. The data were analyzed using the qualitative data analysis model proposed by Miles and Huberman, including data condensation, data display, and conclusion drawing. The analysis was based on Tsui’s (1995) elicitation framework, which classifies elicitation into six types: elicit inform, elicit confirm, elicit agree, elicit commit, elicit repeat, and elicit clarify. The findings revealed that the teacher used four types of elicitation techniques, namely elicit inform, elicit confirm, elicit agree, and elicit repeat. Among these, elicit inform was the most dominant because the teacher frequently used informational questions to check students’ understanding and encourage participation during classroom interaction. The findings also showed that elicitation techniques contributed to increasing students’ participation in English for Nursing learning, although most students’ responses remained short and simple. In addition, elicit commit and elicit clarify were not identified during the observations, indicating that classroom interaction had not fully encouraged elaborative and critical communication. These findings suggest that elicitation techniques play an important role in supporting interactive communication and professional language learning in ESP nursing contexts. Keywords: elicitation techniques; classroom interaction; English for Nursing; English for Specific Purposes.